High-density peptide microarray exploration of the antibody response in a rabbit immunized with a neurotoxic venom fraction. (November 2017) - Engmark, Mikael; Jespersen, Martin C.; Lomonte, Bruno; Lund, Ole; Laustsen, Andreas H.
Abstract: Polyvalent snakebite antivenoms derive their therapeutic success from the ability of their antibodies to neutralize venom toxins across multiple snake species. This ability results from a production process involving immunization of large mammals with a broad suite of toxins present in venoms. As a result of immunization with this wide range of toxins, many polyvalent antivenoms have a high degree of cross-reactivity to similar toxins in other snake venoms – a cross-reactivity which cannot easily be deconvoluted. As a proof of concept, we aimed at exploring the opposite scenario by performing a high-throughput evaluation of the extent of cross-reactivity of a polyclonal mixture of antibodies that was raised against only a single snake venom fraction. For this purpose, a venom fraction containing short neurotoxin 1 (SN-1; Uniprot accession numberP01416, three-finger toxin (3FTx) family), which is the medically most important toxin from the notorious black mamba ( Dendroaspis polylepis ), was employed. Following immunization of a rabbit, a specific polyclonal antibody response was confirmed by ELISA and immunodiffusion. Subsequently, these antibodies were investigated by high-density peptide microarray to reveal linear elements of recognized epitopes across 742 3FTxs and 10 dendrotoxins. This exploratory study demonstrates in a single immunized animal that cross-reactivity between toxins of high similarity may be difficult to obtain when immunizing with a single 3FTx containing venom fraction. Additionally, this study explored the influence of employing different lengths of peptides in high-density peptide microarray experiments for identification of toxin epitopes. Using 8-mer, 12-mer, and 15-mer peptides, a single linear epitope element was identified in SN-1 with high precision. Highlights: Antiserum cross-reactivity may be limited when immunizing with a single neurotoxin. Antibody-toxin binding may be lost upon substitution of one toxin epitope residue. Linear epitope mapping results are consistent when using different peptide lengths.